Muscular pattern in three species of Macrostomum (platyhelminthes, macrostomorpha) - Adami, Mariana Laura (2017)
Previous studies demonstrated complex architecture of the muscular system of Macrostomum species, especially in the rostrum area and the pharynx. However, little is known about the differences in muscular pattern between species of the genus. This study examines and compares the muscular systems of specimens belonging to three freshwater Macrostomum species (M. quiritium, M. tuba and M. velastylum), labeled with phalloidin-rhodamine and studied by confocal microscopy. Our results agree with the previous descriptions, confirming that the muscular patterns for the body wall, rostrum area, pharynx and caudal region differ among species. The muscles of the body wall follow the typical architecture, but the number of fibers in the species analyzed varies between dorsal and ventral surfaces, ranging from 80 to 100 fibers, this record being higher than previous observations. The arrangement of the fibers in the rostrum is complex, especially in the brain area. Macrostomum tuba and M. quiritium have a set of two muscles crossing at brain level and forming an “X,” which is not evident in M. velastylum. We identified five different sets of fibers associated to the pharynx and mouth at ventral, medium and deep levels. These different sets are present in all three species studied. The caudal plate in M. tuba has an additional layer of diagonal fibers in the body wall, which is not evident in the other two species. The muscles of the reproductive system are independent of the body wall musculature in the species analyzed, but connected to the intestinal wall by specific fibers that may serve as an anchor. J. Morphol. 278:264–282, 2017.